Effect of scan time on SMPS particle size measurements - Mohamed A. Altaher; Hu Li (مجلة البيان العلمية, 2023)
This work investigated the effect of scan time of SMPS (Scanning Mobility Particle Sizer) on the stability and shift of ultra-fine and nano-particles measurement. The particles produced from distilled water and salt water (0.020%wt) by an aerosol generator were measured for number concentrations and size distributions using a SMPS. The scanning time of the SMPS was set at 30s, 60s, 120s, 180s and 240s. The filtered compressed air was used to blow through the generator to produce particles. The effect of scanning time on particle numbers and size distributions was compared for each condition. A unimodal size distribution of the particles was found in all the examined conditions. The results showed that a shift of particle size distribution towards smaller particles and lower particle number concentrations with shorter scanning times such as 30s and 60s occurred; indicating that the scanning time affects the particle number and size distribution measurements. The SMPS scanning time should choose to be more than 100s to get reasonably reliable results